Lewis Acid–Base Synergistically Enhancing Practical Composite Electrolyte for Fluoride‐ion Batteries at Room Temperature - Hong Cui; Xiao Gao; Keyu Guo; Wu Liu; Bo Ouyang; Wenbin Yi (Advanced Science, 2025)
Abstract Fluoride‐ion batteries (FIBs) represent a potential “next‐generation” electrochemical storage device, offering high energy density. However, the practical implementation of FIBs at room temperature is impeded by the limitations of currently available ceramic electrolytes. Here, a composite NH4HF2@PEO@β‐PbSnF4 electrolyte with both high conductivity of 10−4 S cm−1 and wide electrochemical stability window (4.59 V vs Pb/PbF2) at room temperature is fabricated. Field emission transmission electron microscope (FETEM) demonstrates the presence of a space charge region, which enhances the conductivity. Furthermore, 19F NMR and density functional theory (DFT) calculations elucidate that the interaction between Sn2+ (Lewis acid) and HF2− (Lewis base) induces significant modifications to the electronic structure, which critically contribute to the enhanced electrochemical stability window of the composite electrolyte. Integrating this promising electrolyte with high‐voltage CuF2 cathodes and Pb/PbF2 anodes, a reversible coin cell with a discharge capacity of 143 mAh g−1 up to 50 cycles is demonstrated. The rational design of such composite electrolytes offers a pathway toward the practical application of FIBs at room temperature.